Students' perceptions of the educational value of Twitter: a mixed-methods investigation - Amanda Deaves; Emily Grant; Kate Trainor; Kathryn Jarvis (Association for Learning Technology, 2019)
It has been suggested that Twitter can be used in healthcare education to enhance active engagement and access to information. However, there is limited information regarding students' perceptions of this platform as a pedagogical tool. This study explored the perceptions of final-year undergraduate physiotherapy students in relation to a dedicated Twitter feed that was used to support learning throughout the academic year. A mixed-methods design was utilised. A total of 33 students participating in pre- and post-surveys and two focus groups (super users and novice users) provided rich data regarding value perceptions. The results indicate that the Twitter feed was a positive addition to teaching/education and provided insights in three themes: digital literacy, educational experience and professional identity. Twitter appeared to add value to the students' educational experience via peer-assisted learning, collaboration and connectivity. Professional identity awareness can impact students' Twitter activity; therefore, consideration regarding the enhancement of self-confidence and active engagement within this platform is recommended.